Penulisan Operasi Hitung dalam Bahasa Inggris melalui Game Take A Number - Riris Sugianto; Baiq Yuni Wahyuningsih; Reny Wardiningsih (ISLAMIKA, 2020)
The implementation of this activity was carried out with the aim of improving the ability of ASM Mataram Banking Administration Management students in writing arithmetic operations using English both in mathematical notation and writing hundreds (hundreds) and thousands (thousands) in English. The stages of this activity begin with the initial stage (preparation), the core stage (implementation) and the final stage (evaluation). The initial stage is the preparation, at this stage the initial observation, the collection of material about the procedures for writing mathematical operations in English both writing mathematical notation and writing numbers in English and is equipped with questions of counting operations in English that are appropriate for the level students. The core stage is the implementation carried out by providing training in writing arithmetic in English through the game take a number for banking administration management students at ASM Mataram. The last stage is the evaluation carried out by giving some questions on the number counting operations in English that are done by students in accordance with the material that has been delivered, and comparing the results of the comparison before and after the training is given. Based on the implementation of the activity, the results showed that the arithmetic operations writing training had a good impact on mathematics and mastery of English. The addition of the game take a number aims to refresh the minds of students so that they can work on the questions while playing, as well as training the foresight, speed and accuracy in listening, writing, counting and adding numbers previously read in English.